Synchronized Pulsatile Flow With Low Systolic Output From Veno‐Arterial Extracorporeal Membrane Oxygenation Improves Myocardial Recovery After Experimental Cardiac Arrest in Pigs. Issue 6 (6th March 2018) - Voicu, Sebastian; Sideris, Georgios; Dillinger, Jean‐Guillaume; Yannopoulos, Demetris; Deye, Nicolas; Kang, Chantal; Bonneau, Michel; Bartos, Jason; Kedra, Antoni; Bailliart, Sophie; Pasteur‐Rousseau, Adrien; Amah, Guy; et al.
Abstract: Circulatory failure following cardiac arrest (CA) requires catecholamine support and occasionally veno‐arterial extracorporeal membrane oxygenation (vaECMO). VaECMO‐generated blood flow is continuous and retrograde, increasing ventricular stroke work. Our aim was to assess the benefit of a device generating a pulsatile vaECMO flow synchronized with the heart rhythm lowering systolic vaECMO output on the left ventricular ejection fraction (LVEF) and pulmonary capillary pressure (Pcap) after CA. This experimental randomized study in pigs compared standard nonpulsatile vaECMO (control) with pulsatile synchronized vaECMO (study) group using a pulsatility‐generating device. After sedation and intubation, ventricular fibrillation was induced by pacing. After 10‐min ventricular fibrillation, cardiopulmonary resuscitation was performed for 20 min then vaECMO, defibrillation and 0.15 µg/kg/min intravenous epinephrine infusion were initiated. Hemodynamics, Pcap, LVEF by echocardiography and angiography were measured at baseline and every 30 min after the vaECMO start until vaECMO and epinephrine were stopped (at 120 min), and 30 min later. Baseline hemodynamics did not differ between groups; 120 min after vaECMO initiation, LVEF by echocardiography and angiography was significantly higher in the study than control group 55 ± 19% versus 34 ± 13% ( P  = 0.042), 50 ± 16% versus 33 ± 12% ( P  = 0.043), respectively. Pcap decreased from baseline by 4.2 ± 8.6 mm Hg in the study group but increased by 5.6 ± 5.9 mm Hg in the control group ( P  = 0.043). Thirty minutes later, LVEF remained higher in the study group 44 ± 7% versus 26 ± 11% ( P  = 0.008) while Pcap did not differ. A synchronized pulsatile device decreasing systolic output from vaECMO improved LVEF and Pcap in a pig model of CA and resuscitation.